A Mixed Methods Study Exploring the Factors and Behaviors That Affect Glycemic Control Following a Structured Education Program: The Irish DAFNE Study. (April 2016) - Casey, Dympna; O'Hara, Mary Clare; Meehan, Ben; Byrne, Molly; Dinneen, Sean F.; Murphy, Kathy
Aim: To explain the factors affecting glycemic control (measured by HbA1c) following the Dose Adjustment for Normal Eating (DAFNE) program.Background: DAFNE is a structured education program designed to assist persons with type 1 diabetes mellitus achieve optimal glycemic control. However, not all participants reach this goal. Few studies comprehensively explain why this is the case.Research Design: A concurrent mixed methods design. Data were collected from participants ( n = 34) at three time points post DAFNE in five participating sites. Each data set was analyzed separately and then integrated.Results: Motivation and support differed for participants who were out of control and those in control.Conclusion: Setting targets/goals and motivations are key in helping participants attain optimal HbA1c.